Academic Women: Lived Experiences in Contexts of Inequality - Sancho-Gil, Juana M.; Hernández - Hernández, Fernando (Acta Paedagogica Vilnensia, 2018)
[full article in English]This article builds on the results of a research project into the professional experience of seven academic women in universities and research centers in Catalonia, Spain. The aim of the Project was to explore the personal and professional experience of three generations of women in the process constituting their identity as university teachers, researchers and managers. The writing of their professional life histories has enabled us to investigate how they, as women, have become the types of higher education teachers, researchers and managers that they were becoming, and we wished to delve into the relationship between their personal experiences and the development of their professional careers. In this process, we have revealed the strategies of adaptation, resistance and creation developed by women, the forms of symbolic violence that they experience and the changes through which their careers have passed within the context of an institution that is still continuously revealed by different studies to be deeply discriminating and unequal for women.
Keywords: higher education, gender politics, life histories, university teacher identity, researcher identity